Pancreatoduodenectomy for Periampullary Tumors Presenting with Acute Pancreatitis - Xuefeng Cao; Xixiu Wang; Xiaoliang Xu; Yanmin Lu; Baolei Zhao; Xingyuan Zhang; Qiangpu Chen (Gastroenterology Research and Practice)
Background. Periampullary tumors (PT) may rarely present as acute pancreatitis (AP) or acute recurrent pancreatitis (ARP). Unlike other cases of AP and ARP, these conditions necessitate pancreaticoduodenectomy (PD), and timely diagnosis is crucial. Materials and Methods. A retrospective review of clinical, radiological, surgical, and pathological data was conducted for patients admitted to the Binzhou Medical University Hospital during the period from January 2010 to December 2017, for AP or ARP caused by PT. All patients included in the study group had undergone PD. The perioperative data for these patients was compared with data for patients with PT but without AP or ARP who underwent PD during the same period (control group). Results. During the study period, 412 patients with AP or ARP were treated; among this group, 15 patients had PT. Compared with controls, patients in the study group were younger in age and had a longer course of disease, more frequent hospitalizations, and more severe derangements in laboratory data (P<0.05). Operative time and intraoperative blood loss were significantly higher in the study group, but the incidence of postoperative outcomes such as pancreatic/biliary fistula, abdominal infection, postoperative hospital stay, and mortality were similar between groups (P>0.05). Conclusions. Neither AP nor ARP has any adverse impact on the outcomes of PD. However, in the treatment of younger patients suffering from AP or ARP, unexplained pancreatic duct dilation and weight loss should raise the suspicion of PT. EUS and EUS-FNA may be helpful in making the diagnosis.